51.2k views
3 votes
Factor completely 16x^8 − 1.

2 Answers

5 votes

Answer:

(2x² - 1)(2x² + 1)(4
x^(4) + 1)

Explanation:

16
x^(8) - 1 ← is a difference of squares and factors in general as

a² - b² = (a - b)(a + b), thus

16
x^(8) - 1

= (4
x^(4) )² - 1²

= (4
x^(4) - 1)(4
x^(4) + 1) ← 4x
x^(4) - 1 is also a difference of squares

4
x^(4) - 1

= (2x² )² - 1²

= (2x² - 1)(2x² + 1)

Thus

16
x^(8) - 1 = (2x² - 1)(2x² + 1)(4
x^(4) + 1)

User Cabesuon
by
6.1k points
6 votes

Answer:

(4x^4 + 1) (2x^2 + 1) (2x^2 - 1)

Explanation:

User Danseethaler
by
5.0k points